PERANCANGAN BUKU POP-UP CERITA RAKYAT BAGUS KUNING UNTUK ANAK-ANAK - Syaroful Anam; Husni Mubarat; Didiek Prasetya (UNIVERSITAS INDO GLOBAL MANDIRI, 2018)
The design of visual communication media is basically one of the efforts that can be done to preserve the folklore in the city of palembang. Bagus Kuning folklore is one of the folklore in South Sumatra. Ratu Bagus Kuning is a title, the original name of Putri Mulia Syarifah Mahani. Still descendants of Syaidi Syech Zain Al-Abid Yemen (Syech Zainal Abidin Madina RA Son Syaidina Husain RA Son Syaidina Ali Karamullah Wajha with first wife Siti Fatimah Az-Zahro Binti Muhammad SAW). Although she is a woman, her leadership can be an example and to be liked by everyone. He is the local ruler who is domiciled on the coast of the river Musi named Ratu Bagus Kuning. That said, he is one of the disciples of nine guardians on the island of Java known as Walisongo. His presence in Palembang was to spread Islam. The interest of the writer raised this theme seen from the moral message possessed by Bagus Kuning. Visual Communication Media Design aims to introduce the folklore in the city of Palembang his special folklore Good Yellow to children in the city of Palembang for this folktale is more widely known by the public as well as a destination for educational, religious, historical and cultural .It is in need of effective and efficient promotion media. The design of this visual communication media is book designed in such a way based on media problem. Promotion very less in Palembang city, this aims at achieving promotion creatively and easily digested. Keywords: Folklore, Pop-up Books, Bagus Kuning.